Video analysis of rolling cylinders - S. Phommarach (2018)
In this work, we studied the rolling motion of solid and hollow cylinders down an inclined plane at different angles. The motions were captured on video at 300 framess -1, and the videos were analyzed frame by frame using video analysis software. Data from the real motion were compared with the theory of rolling down an inclined plane without slipping. From the experiment, the acceleration does not depend on the cylinder mass as indicated from the theory. For the wood-steel surface, we found that the coefficient of static friction was equal to 0.131 and the critical angle for the solid cylinder was 21.45°. The critical angle for the hollow cylinder depends on the inner and outer radius of the cylinder. Motion paths of a point on the hollow cylinder at small and large angles were shown to elucidate the pure rolling condition. Finally, we demonstrated that total mechanical energy was conserved during the pure rolling motion. This confirms that work done by the friction force is zero. We will use these results to design an interactive lecture demonstration on rolling without slipping. © 2012 IOP Publishing Ltd.